Phytochemical Analysis and Antimicrobial Activity of Smilax ovalifoliaRoxb. Ex D. Don - Paneru, Damaru Prasad; Rajbhandari, Meena (Nepal Journal of Science and Technology, 2020)
Hexane, dichloromethane, ethyl acetate, methanol and 50% aqueous methanol extracts of S. ovalifolia were screened for the presence of different classes of phytochemicals as well as their antibacterial activity. The phytochemical screening revealed the presence of phenolic, flavonoid and carbohydrate in methanol and 50% aqueous methanol extracts of S. ovalifolia. The antibacterial susceptibility was studied against E. coli and S. aureus. Among all the tested extracts, ethyl acetate extract showed good antibacterial activity against both bacteria. In the methanol and 50%, aqueous methanol extracts of S. ovalifolia, total phenolic, total flavonoid and total carbohydrate content were estimated, and free radical scavenging activity was determined. Total phenolic content was measured spectrophotometrically by using Folin- Ciocalteu reagent, total flavonoid content by using aluminium chloride and total carbohydrate content by using the anthrone method. Gallic acid was used as the standard for the calibration of phenolics, catechin for flavonoids and glucose for carbohydrates. The highest amount of phenolic and flavonoid were found in methanol extract (192.152±0.009 mg GAE/g extract and 78.188±2.719 mg CE/g extract), respectively. The highest amount of sugar was found in 50% methanol extract (190.585±2.445 mg GE/g extract). Methanol extract also showed good antioxidant activity (IC50 value 49.989 μg/ml) than 50% aqueous methanol extract (IC50 72.021 μg/ml). The GC-MS analysis of hexane extract of S. ovalifolia allowed the identification of 16 phyto-constituents based on retention time and the fragmentation pattern in the mass spectrum.